Implementation of Local Wisdom in Folklore Toraja Landorundun - Dina Gasong (Teaching English as a Foreign Language Overseas Journal, 2016)
This article describes the implementation of didactic values, social values, and psychological values in folklore Toraja Landorundun encountered in everyday life. The research methodology used is descriptive qualitative research. Respondents of this study consists of cultural, educational practitioners, and religious leaders (Pastor). Criterion validity of the data that will be used by researchers, among others: the degree of trust, (credibility), transferability, dependability, and confirmability. Implementation folklore values Landorundun Toraja in everyday life, namely the value of education: (1) To promote cooperation and good relations between other tribes, (2) advising and admonishing when malice, (3) the nature of mutual cooperation Embedding (good cooperation within the community, school and family ). (4) Always help the weak. (5) Respect the customs that have been agreed upon. (6) For the younger generation to learn to work hard to achieve the highest ideals . Social values, namely the implementation of the terms proposed by Landorundun is very hard. Based on this type of Toraja people are hard workers who are fighting in the capital to other areas. People are still looking for a matching pair (family equivalent) . Imlementasi Psychological values in public life thanks to Toraja eg parents of children be respected, otherwise handicapped child in the family considered parents fault. Selfesteem, women have self-esteem, which is worthy of respect, because it is men who woo women .